MOUNTAIN CARIBOU INTERACTIONS WITH WOLVES AND MOOSE IN CENTRAL BRITISH COLUMBIA - Seip, Dale R (Lakehead University, 2008)
Mountain caribou (Rangifer tarandus caribou) populations in south-eastern British Columbia are declining over most of their range and are listed as Threatened. Predation has been documented as the major cause of declining caribou numbers. Excessive predation by wolves (Canis lupus) has been related to increased moose (Alces alces) numbers. The increase in moose appears to be the result of a natural colonization process that has been enhanced by human-caused habitat change. Options to reduce the rate of predation include reducing wolves, reducing moose, and reducing the amount of early seral habitat that supports moose. Current management includes population control of moose and wolves. Monitoring and assessment of these approaches will guide the future management strategy used to maintain mountain caribou in south-eastern British Columbia.